Advanced Phosphorus‐Based Materials for Lithium/Sodium‐Ion Batteries: Recent Developments and Future Perspectives. Issue 13 (29th January 2018) - Fu, Yanqing; Wei, Qiliang; Zhang, Gaixia; Sun, Shuhui
Abstract: High‐performance and lost‐cost lithium‐ion and sodium‐ion batteries are highly desirable for a wide range of applications including portable electronic devices, transportation (e.g., electric vehicles, hybrid vehicles, etc.), and renewable energy storage systems. Great research efforts have been devoted to developing alternative anode materials with superior electrochemical properties since the anode materials used are closely related to the capacity and safety characteristics of the batteries. With the theoretical capacity of 2596 mA h g −1, phosphorus is considered to be the highest capacity anode material for sodium‐ion batteries and one of the most attractive anode materials for lithium‐ion batteries. This work provides a comprehensive study on the most recent advancements in the rational design of phosphorus‐based anode materials for both lithium‐ion and sodium‐ion batteries. The currently available approaches to phosphorus‐based composites along with their merits and challenges are summarized and discussed. Furthermore, some present underpinning issues and future prospects for the further development of advanced phosphorus‐based materials for energy storage/conversion systems are discussed. Abstract : Phosphorus has been considered as one of the most potentially promising anode materials for both lithium‐ion and sodium‐ion batteries due to its abundant reserve and high theoretical capacity (2596 mA h g −1 ) . Up to now, many relevant papers have been published. This work offers a comprehensive review of up‐to‐date advances and future perspectives on red/black phosphorus‐based materials for lithium/sodium‐ion batteries.